Cellular polyamines influence maturation and germination of somatic embryos from pro-embryonal masses of two grapevine cultivars - Nookapaju, A.; Barreto, M. S.; Agrawal, Dinesh C. (Vitis, 2008)
Somatic embryos of grapevine multiply repeatedly and often fail to mature and germinate due to factors like dormancy and embryo teratology. The present investigation was carried out to improve the maturation and germination of somatic embryos from pro-embryonal masses (PEM) of 2A-Clone and `Crimson Seedless', two seedless grapevine cultivars. Also, the aim was to study a correlation between cellular and residual polyamine (PA) levels in PEM and culture media. The efficiency of maturation and germination of embryos from PEM varied significantly between the two cultivars and depended on incubation period and type of PAs in the medium. HPLC analysis showed that higher levels of cellular putrescine in PEM had correlation with maturation and germination percentages in both cultivars. The levels of three PAs depleted in the media rapidly indicating its uptake by PEM. Of the three PAs, putrescine (PUT) was the most effective and resulted in 100.0 or 92.0 % maturation at 14 d or 30 d in 2A-Clone or `Crimson Seedless', respectively. The maximum germination of somatic embryos was recorded with PUT at 14 d or 21 d in 2A-Clone or `Crimson Seedless', respectively.
Keywords: germination; Grapevine; maturation; polyamines; `2A-Clone'; `Crimson Seedless'